A Comparative Study of Lipid Profile and Atherogenic Index of Plasma Among the Pre and Post-Menopausal Women (Anwer Khan Modern Medical College Journal, 2018)
Background: Menopausal health in our environment has received little attention. As a independent risk factor for dyslipidemia, the degree and pattern of derangement, though difficult to assess may adversely affect the cardiovascular health of our women.Objectives: To estimate the serum lipid profile and the atherogenic index of plasma among the pre and post- menopausal women.Materials and Methods: After an overnight fasting blood samples were collected from a group of 339 women, 140 premenopausal aged between 25-50 years and 199 postmenopausal aged between 51-70 years. Serum total cholesterol (TC), triglycerides (TG) and HDL-cholesterol were estimated by enzymatic methods and LDL-cholesterol by established mathematical methods. Atherogenic index of plasma (AIP) were calculated by using the formula (logTG/HDL-C). Statistical analysis was carried out in the two groups using the unpaired t test. Results were expressed as mean±SD. P values